Influence of Media Leaflets on the Mother's Behaviour on the Language Development of the Child - Sari, Fitria Dila; Deswita, Deswita; Fajria, Lili (LPPM Universitas Prima Nusantara Bukittinggi, 2023)
Background: Language development is vital in toddlerhood. In Indonesia, language and speech delays in children aged 36–48 months range from 5–10%.Objective: This study aims to see the effect of leaflet media on the knowledge and attitudes of mothers.Method: This quantitative research uses the research design